Photocuring forming preparation method of high-strength fused quartz ceramic

By introducing SiC powder into the fused quartz powder and using its oxidation reaction to generate SiO2, the problems of excessive curing depth and low sintering density in photocuring of fused quartz ceramics are solved, and the molding accuracy and sample strength are improved.

CN119118638APending Publication Date: 2024-12-13NAT INST CORP OF ADDITIVE MFG XIAN
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411258152.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the traditional photocuring 3D printing process of fused quartz ceramic, the curing depth is too large due to the good light transmittance of fused quartz, which affects the molding accuracy, and the sintering density is low, resulting in poor strength.

Method used

Silicon carbide (SiC) powder is introduced into the fused quartz powder, and SiO2 is generated through blending and oxidation reaction, which increases the sintering density and reduces the curing depth by the high absorbance of SiC.

Benefits of technology

It effectively reduces the curing depth of fused quartz ceramics, improves the sintering density and sample strength, and solves the problem of insufficient molding accuracy and strength in traditional processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005034710590000011
    Figure HDA0005034710590000011
  • Figure HDA0005034710590000012
    Figure HDA0005034710590000012
Patent Text Reader

Abstract

The invention discloses a photocuring forming preparation method of high-strength fused quartz ceramic, and belongs to the technical field of photocuring forming. Comprising the following steps: blending fused quartz powder with a modifier I and a modifier II to prepare mixed powder, performing wet grinding, drying and sieving to obtain modified fused quartz powder; mixing the prepolymer I, the prepolymer II, a resin monomer I, a resin monomer II, a photoinitiator I and a photoinitiator II to prepare a photosensitive resin system; adding a dispersing agent into the photosensitive resin system, uniformly mixing, then adding the modified fused quartz powder and SiC powder, and uniformly mixing, so as to prepare fused quartz ceramic photocuring slurry; carrying out printing forming, degreasing treatment and sintering on the fused quartz ceramic photocuring slurry to obtain fused quartz ceramic; the use amount of the SiC powder is 1wt%-5wt% of the mass of the modified fused quartz powder. The preparation method can reduce the curing depth of the fused quartz, improve the forming precision and improve the sintering density of the fused quartz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocuring molding, and in particular relates to a photocuring molding preparation method for high-strength fused quartz ceramics. Background Art

[0002] Radome is a protective device for aircraft radar antennas, integrating wave transmission, load bearing, and temperature resistance. Fused quartz ceramics have the advantages of low thermal expansion coefficient, good thermal shock resistance, excellent dielectric properties, and good thermal shock resistance, and have become one of the main candidate materials for radar covers in the defense and military fields. However, the traditional preparation process of fused quartz radomes is time-consuming, technically demanding, and labor-intensive. Ceramic light-curing 3D printing technology has become a boon for the preparation of fused quartz radomes with its high molding efficiency, good molding accuracy, and high model freedom.

[0003] Ceramic photocuring 3D printing technology uses ceramic powder-photosensitive resin blend slurry as raw materials. According to the designed 3D model, the ceramic green body is prepared by layer-by-layer printing and molding by photocuring 3D printing equipment. The green body is then degreased, and the organic components are removed and then sintered at high temperature to obtain the required three-dimensional ceramic sample. However, due to the good light transmittance of fused quartz, the single-layer curing depth is very high, which will cause over-curing during the printing process, thereby affecting the accuracy of the molded parts; in addition, the fused quartz ceramics prepared by photocuring 3D printing currently have a low sintering density, resulting in poor strength, which limits its application in actual production. Summary of the invention

[0004] In order to overcome the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a photocuring molding preparation method for high-strength fused quartz ceramics, which can reduce the solidification depth of fused quartz, improve molding accuracy, and increase the sintering density of fused quartz.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing high-strength fused quartz ceramic by photocuring, comprising the following steps:

[0007] S1: blending fused quartz powder with modifier 1 and modifier 2 to obtain a mixed powder, then wet-grinding, drying and sieving to obtain modified fused quartz powder;

[0008] S2: Prepolymer 1, prepolymer 2, resin monomer 1, resin monomer 2, photoinitiator 1, and photoinitiator 2 are mixed to prepare a photosensitive resin system; a dispersant is added to the photosensitive resin system and mixed evenly, and then modified fused quartz powder and SiC powder are added and mixed evenly to prepare a fused quartz ceramic photocuring slurry;

[0009] S3: Printing and molding the fused quartz ceramic photocuring slurry to obtain a fused quartz ceramic green body;

[0010] S4: degreasing the fused quartz ceramic green body to obtain a fused quartz degreasing part;

[0011] S5: sintering the degreased fused quartz piece to obtain fused quartz ceramics;

[0012] Wherein, S2, the amount of SiC powder is 1wt% to 5wt% of the mass of the modified fused quartz powder.

[0013] In one embodiment, in S1, the modifier 1 is one or more of KH550, KH560, KH570, stearic acid, oleic acid, palmitic acid, and adipic acid; the amount of the modifier 1 is 1wt% to 6wt% of the mass of the modified fused quartz powder;

[0014] The second modifier is one or more of polyethylene, polypropylene, polyacrylamine, polymaleic acid, polyethylene glycol, polyacrylic acid, and sodium polyacrylate; the amount of the second modifier is 1wt% to 6wt% of the mass of the modified fused quartz powder.

[0015] In one embodiment, in S2, the solid content of the fused silica ceramic photocurable slurry is 55 vol% to 65 vol%.

[0016] In one embodiment, in S2, the particle sizes of the modified fused silica powder and the fused silica powder are both 1 to 5 μm; and the particle size of the SiC powder is 200 to 500 nm.

[0017] In one embodiment, in S2, the prepolymer 1 is one or more of bisphenol A diglycidyl ether, brominated bisphenol F diglycidyl ether, polyurethane acrylate, and polyester acrylate; the prepolymer 2 is one or more of triethylene glycol divinyl ether, cyclohexyl-1,4-dimethanol vinyl ether, and vinyl acetate; the resin monomer 1 is one or more of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, and pentaerythritol tetraacrylate; and the resin monomer 2 is one or more of isobornyl methacrylate, tripropylene glycol diacrylate, and dipentaerythritol hexaacrylate.

[0018] In one embodiment, in S2, the ratio of prepolymer 1, prepolymer 2, resin monomer 1, and resin monomer 2 is 1:3:8:8.

[0019] In one embodiment, in S2, the photoinitiator 1 is one or both of 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide; the photoinitiator 2 is one or more of phenyl diazonium fluoroborate, diaryl iodonium salt, triaryl sulfonium salt and benzoin dimethyl ether.

[0020] In one embodiment, in S2, the mass ratio of the photoinitiator 1 to the photoinitiator 2 is 1.5-2.5:0.5-1.5; the total amount of the photoinitiator 1 and the photoinitiator 2 is 1wt%-5wt% of the total mass of the photosensitive resin system.

[0021] In one embodiment, in S2, the dispersant is selected from Solsperse TM 29000, Solsperse TM W210, Solsperse TM W75, Solsperse TM AC5160, Solsperse TM AC4380, the amount of the dispersant is 2wt% to 8wt% of the mass of the modified fused quartz powder.

[0022] In one embodiment, in S3, the printing is performed using a DLP light-curing device;

[0023] In S4, the degreasing process is as follows:

[0024] Under argon atmosphere, the maximum degreasing temperature is 650-800°C, the heating rate is 0.1-0.2°C / min, the holding time is 120min, and the furnace is cooled;

[0025] In S5, the sintering process is as follows:

[0026] In an air environment, the sintering temperature is 1150°C to 1400°C, the heating rate is 0.5 to 1°C / min, the holding time is 120 to 180 minutes, and the furnace is cooled.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention provides a method for preparing high-strength fused quartz ceramic by photocuring. Silicon carbide (SiC) is introduced into fused quartz powder to reduce the curing depth and improve the density. SiC particles, as a dark ceramic powder, can be regarded as an inorganic dye. The absorbance of the ceramic slurry is increased by adding and blending, and the penetration of ultraviolet light is reduced, so as to finally reduce the curing depth. At the same time, SiC will begin to undergo oxidation reaction at high temperature to generate SiO2 in situ. The newly generated SiO2 can connect the original SiO2 particles that are not sintered and dense in the matrix, so as to improve the sintering density. In summary, the present invention provides a method for preparing ceramic photocuring by introducing SiC as an inorganic dye to reduce the curing depth and improve the sintering density. It can solve the technical problem that fused quartz produces over-curing phenomenon during printing, thereby affecting the precision of the molded part, and the technical problem that the fused quartz ceramic prepared by photocuring 3D printing has low sintering density, resulting in poor strength.

[0029] In summary, compared with the ceramic preparation method of adding SiC to fused quartz ceramic powder commonly used in the prior art, the present invention utilizes the high absorbance of SiC to solve the problem of high curing depth in the fused quartz photocuring 3D printing process, and generates SiO2 in situ through the oxidation behavior of SiC during atmospheric sintering, which has a connecting effect on the original SiO2 particles, thereby improving the sintering density of the fused quartz and the strength of the sample. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a degreasing curve diagram of a fused quartz part made by using the photo-stereolithography technology in Example 1 of the present invention;

[0031] Figure 2 This is a sintering curve diagram of a fused quartz product made by using the photo-stereolithography technology in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0033] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0034] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0035] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0036] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0037] The present invention provides a method for preparing high-strength fused quartz ceramic by photocuring, into which a method for preparing SiC-reinforced fused quartz ceramic by photocuring is introduced, comprising the following steps:

[0038] S1. Powder modification: Blending fused quartz powder with modifier 1 and modifier 2 to obtain mixed powder, and obtaining modified fused quartz powder after drying and sieving.

[0039] S2. Preparation of fused quartz ceramic photocuring slurry: The photosensitive resin system is prepared by mixing prepolymer 1, prepolymer 2, resin monomer 1, resin monomer 2, photoinitiator 1 and photoinitiator 2.

[0040] The dispersant is added to the photosensitive resin system and mixed evenly, and then the modified fused quartz powder obtained in step S1 is added and mixed evenly with the SiC powder to obtain a fused quartz ceramic photocuring slurry.

[0041] S3, photocuring 3D printing: using DLP photocuring equipment to print and shape the fused quartz ceramic photocuring slurry obtained in step S2 to obtain a fused quartz ceramic green body.

[0042] S4, green body degreasing: the fused quartz ceramic green body obtained in step S3 is degreased according to the established process to obtain a fused quartz degreased part.

[0043] S6, sintering of fused quartz ceramics: sintering the degreased fused quartz piece obtained in step S4 according to a specified process to obtain fused quartz ceramics.

[0044] As a preferred embodiment, the specific dosage of the above method is:

[0045] In one embodiment, the wet grinding is performed by adding alcohol, the wet grinding time is 10 to 15 hours, and the mass ratio of alcohol to mixed powder is 1:1 to 1.5.

[0046] In one embodiment, the dispersant is added to the photosensitive resin system and mixed evenly, and homogenized with a homogenizer at a speed of 800 r / min to 1500 r / min for 30 to 60 seconds. The modified fused quartz powder obtained in step S1 is mixed evenly with the SiC powder, and homogenized with a homogenizer at a speed of 1000 r / min to 2000 r / min for 1 to 3 minutes.

[0047] In one embodiment, the solid content of the fused quartz ceramic photocuring slurry is 55 vol% to 65 vol%; the particle sizes of the fused quartz powder and the modified fused quartz powder are both 1 to 5 μm, and the particle size of the SiC powder is 200 to 500 nm; the amount of the SiC powder is 1 wt% to 5 wt% of the mass of the modified fused quartz powder.

[0048] In one embodiment, the modifier 1 is selected from one or more of KH550, KH560, KH570, stearic acid, oleic acid, palmitic acid, and adipic acid, and the amount used is 1wt% to 6wt% of the mass of the modified fused quartz powder; the modifier 2 is selected from one or more of polyethylene, polypropylene, polyacrylamine, polymaleic acid, polyethylene glycol, polyacrylic acid, and sodium polyacrylate, and the amount of the modifier 2 is 1wt% to 6wt% of the mass of the modified fused quartz powder.

[0049] In one embodiment, the prepolymer 1 is selected from one or more of bisphenol A diglycidyl ether, brominated bisphenol F diglycidyl ether, polyurethane acrylate (PUA), polyester acrylate (PEA); the prepolymer 2 is selected from one or more of triethylene glycol divinyl ether, cyclohexyl-1,4-dimethanol vinyl ether and vinyl acetate; the resin monomer 1 is selected from one or more of 1,6-hexanediol diacrylate (HDDA), trimethylolpropane triacrylate (TMPTA), pentaerythritol tetraacrylate (PPTTA); the resin monomer 2 is selected from one or more of isobornyl methacrylate (IBOMA), tripropylene glycol diacrylate (TPGDA), dipentaerythritol hexaacrylate (DPHA). The ratio of prepolymer 1, prepolymer 2, resin monomer 1 and resin monomer 2 is 1:3:8:8.

[0050] In one embodiment, the photoinitiator 1 is one or two of 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide (TPO) and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide (819); the photoinitiator 2 is one or more of phenyl diazonium fluoroborate, diaryl iodonium salt, triaryl sulfonium salt and benzoin dimethyl ether, the ratio of the two photoinitiators is 1.5-2.5:0.5-1.5, and the total amount is 1wt% to 5wt% of the total mass of the photosensitive resin system.

[0051] In one embodiment, the dispersant is selected from Solsperse TM 29000, Solsperse TM W210, Solsperse TM W75, Solsperse TM AC5160, Solsperse TM AC4380, the amount of the dispersant is 2wt% to 8wt% of the mass of the modified fused quartz powder.

[0052] In one embodiment, the debinding process is as follows: under an argon atmosphere, the maximum debinding temperature is 650-800° C., the heating rate is 0.1-0.2° C. / min, the holding time is 120 min, and the furnace is cooled.

[0053] In one embodiment, the sintering process is as follows: in an air environment, the sintering temperature is 1150°C to 1400°C, the heating rate is 0.5 to 1°C / min, the holding time is 120 to 180 minutes, and the furnace is cooled.

[0054] The two core innovations of the present invention are: first, the development of a photocurable 3D printing fused quartz slurry with SiC as a reinforcing phase and inorganic dye function; second, the proposal of an innovative fused quartz densification method, which is based on the oxidation reaction of SiC during the sintering process to generate SiO2 in situ, thereby effectively connecting the original SiO2 particles to achieve material densification.

[0055] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0056] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0057] Embodiment 1:

[0058] 1) Powder modification: 2 μm fused quartz powder was blended with 2.5 wt% KH570 and 2 wt% polyethylene glycol, and wet-milled for 12 h with alcohol added, the mass ratio of alcohol to powder being 1:1. The modified fused quartz powder was obtained after drying and sieving.

[0059] 2) Preparation of photocurable slurry: The solid content of the photocurable slurry is 65 vol%; the photosensitive resin system is composed of a prepolymer of bisphenol A diglycidyl ether, polyurethane acrylate (PUA), a prepolymer of dicyclohexyl-1,4-dimethanol vinyl ether, a resin monomer of 1,6-hexanediol diacrylate (HDDA), trimethylolpropane triacrylate (TMPTA), a resin monomer of tripropylene glycol diacrylate (TPGDA), a photoinitiator of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide (TPO), and a photoinitiator of diaryliodonium salt, wherein the ratio of prepolymer 1, prepolymer 2, resin monomer 1 and resin monomer 2 is 1:3:8:8, the ratio of photoinitiator 1 to photoinitiator 2 is 2:1, and the total amount of photoinitiator 1 and photoinitiator 2 is 2wt% of the total mass of the photosensitive resin system; 4wt% of the dispersant Solsperse TM 29000 was added to the photosensitive resin system, and homogenized for 30 seconds with a homogenizer at a speed of 1000 r / min. Then, the modified fused quartz powder obtained in step 1) and 200 nm SiC powder were added, and the amount of SiC powder was 5wt% of the mass of the modified fused quartz powder. The mixture was homogenized for 2 minutes with a homogenizer at a speed of 2000 r / min to obtain a fused quartz ceramic photocuring slurry.

[0060] 3) Photocuring 3D printing: using DLP photocuring equipment to print and shape the fused quartz photocuring slurry obtained in step 2) to obtain a fused quartz ceramic green body.

[0061] 4) Degreasing of green body: Under argon atmosphere, heat to 180℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 250℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 300℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 500℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 600℃ at a rate of 0.1℃ / min, keep warm for 120min, finally heat to 700℃ at a rate of 0.2℃ / min, keep warm for 120min, cool with the furnace to complete degreasing.

[0062] 5) Ceramic sintering: In an air atmosphere, the temperature was raised to 600°C at a rate of 0.5°C / min, kept at this temperature for 180 min, then raised to 1300°C at a rate of 1°C / min, kept at this temperature for 180 min, and cooled in the furnace to obtain fused quartz ceramics with a flexural strength of 48.7 MPa.

[0063] This embodiment is implemented by Figure 1 and Figure 2 The debinding sintering process curve shown is used for heat treatment.

[0064] Embodiment 2:

[0065] 1) Powder modification: 3 μm fused quartz powder was blended with 2 wt% KH550 and 3 wt% polyacrylamine, and wet-milled for 10 h with alcohol added, the mass ratio of alcohol to powder being 1:1. The modified fused quartz powder was obtained after drying and sieving.

[0066] 2) Preparation of photocurable slurry: The solid content of the photocurable slurry is 60 vol%; the photosensitive resin system is composed of a prepolymer of bisphenol A diglycidyl ether, a prepolymer of dicyclohexyl-1,4-dimethanol vinyl ether, a resin monomer of pentaerythritol tetraacrylate (PPTTA), a resin monomer of isobornyl dimethacrylate (IBOMA), a tripropylene glycol diacrylate (TPGDA), a photoinitiator of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide (TPO), and a photoinitiator of dibenzoin dimethyl ether, wherein the ratio of prepolymer 1, prepolymer 2, resin monomer 1 and resin monomer 2 is 1:3:8:8, the ratio of photoinitiator 1 to photoinitiator 2 is 2.5:0.5, and the total amount of photoinitiator 1 and photoinitiator 2 is 5 wt% of the total mass of the photosensitive resin system; 2 wt% of the dispersant Solsperse TMW75 was added to the photosensitive resin system and homogenized at a speed of 1000 r / min for 45 s using a homogenizer. Then, the modified fused quartz powder obtained in step 1) and 300 nm SiC powder were added. The amount of SiC powder was 3 wt % of the mass of the modified fused quartz powder. The system was homogenized at a speed of 1800 r / min for 1 min using a homogenizer to obtain a fused quartz ceramic photocuring slurry.

[0067] 3) Photocuring 3D printing: using DLP photocuring equipment to print and shape the fused quartz photocuring slurry obtained in step 2) to obtain a fused quartz ceramic green body.

[0068] 4) Degreasing of green body: Under argon atmosphere, heat to 220℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 280℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 340℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 520℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 600℃ at a rate of 0.1℃ / min, keep warm for 120min, finally heat to 750℃ at a rate of 0.2℃ / min, keep warm for 120min, cool with the furnace to complete degreasing.

[0069] 5) Ceramic sintering: In an air atmosphere, the temperature was raised to 600°C at a rate of 0.5°C / min, kept at this temperature for 180 min, then raised to 1150°C at a rate of 1°C / min, kept at this temperature for 120 min, and cooled in the furnace to obtain fused quartz ceramics with a flexural strength of 40.6 MPa.

[0070] Embodiment 3:

[0071] 1) Powder modification: 5 μm fused quartz powder was blended with 1 wt % oleic acid and 3.5 wt % polymaleic acid, and wet-milled for 15 h with alcohol added, the mass ratio of alcohol to powder being 1:1.5. The modified fused quartz powder was obtained after drying and sieving.

[0072] 2) Preparation of photocurable slurry: The solid content of the photocurable slurry is 58 vol%; the photosensitive resin system is composed of a prepolymer of brominated bisphenol F diglycidyl ether, a prepolymer of diethylene glycol divinyl ether, a resin monomer of 1,6-hexanediol diacrylate (HDDA), a resin monomer of isobornyl dimethacrylate (IBOMA), a photoinitiator of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (819), and a photoinitiator of ditriaryl sulfonate, wherein the ratio of prepolymer 1, prepolymer 2, resin monomer 1 and resin monomer 2 is 1:3:8:8, the ratio of photoinitiator 1 to photoinitiator 2 is 1.5:1, and the total amount of photoinitiator 1 and photoinitiator 2 is 1wt% of the total mass of the photosensitive resin system; 8wt% of the dispersant Solsperse TM W210 was added to the photosensitive resin system and homogenized at a speed of 1200 r / min for 45 s using a homogenizer. Then, the modified fused quartz powder obtained in step 1) and 200 nm SiC powder were added. The amount of SiC powder was 3 wt% of the mass of the modified fused quartz powder. The system was homogenized at a speed of 1500 r / min for 1.5 min using a homogenizer to obtain a fused quartz ceramic photocuring slurry.

[0073] 3) Photocuring 3D printing: using DLP photocuring equipment to print and shape the fused quartz photocuring slurry obtained in step 2) to obtain a fused quartz ceramic green body.

[0074] 4) Degreasing of green body: Under argon atmosphere, heat to 200℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 300℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 380℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 550℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 600℃ at a rate of 0.1℃ / min, keep warm for 120min, finally heat to 700℃ at a rate of 0.2℃ / min, keep warm for 120min, cool with the furnace to complete degreasing.

[0075] 5) Ceramic sintering: In an air atmosphere, the temperature was raised to 600°C at a rate of 0.5°C / min, kept at this temperature for 180 min, then raised to 1400°C at a rate of 1°C / min, kept at this temperature for 150 min, and cooled in the furnace to obtain fused quartz ceramics with a flexural strength of 46.5 MPa.

[0076] Embodiment 4:

[0077] 1) Powder modification: 1 μm fused quartz powder was blended with 3 wt % palmitic acid and 3 wt % sodium polyacrylate, and wet-milled for 11 h with alcohol added, wherein the mass ratio of alcohol to powder was 1:1. The modified fused quartz powder was obtained after drying and sieving.

[0078] 2) Preparation of photocurable slurry: The solid content of the photocurable slurry is 55 vol%; the photosensitive resin system is composed of a prepolymer of brominated polyester acrylate (PEA), a prepolymer of vinyl acetate, a resin monomer of trimethylolpropane triacrylate (TMPTA), a resin monomer of dipentaerythritol hexaacrylate (DPHA), a photoinitiator of phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide (819), and a photoinitiator of diphenyl diazonium fluoroborate, wherein the ratio of prepolymer 1, prepolymer 2, resin monomer 1 and resin monomer 2 is 1:3:8:8, the ratio of photoinitiator 1 to photoinitiator 2 is 2.5:1.5, and the total amount of photoinitiator 1 and photoinitiator 2 is 3 wt% of the total mass of the photosensitive resin system; 5 wt% of the dispersant Solsperse TM AC5160 was added to the photosensitive resin system and homogenized at a speed of 1000 r / min for 60 s using a homogenizer, and then the modified fused quartz powder obtained in step 1) and 500 nm SiC powder were added, with the amount of SiC powder being 1 wt% of the mass of the modified fused quartz powder. The system was homogenized at a speed of 1500 r / min for 1 min using a homogenizer to obtain a fused quartz ceramic photocuring slurry.

[0079] 3) Photocuring 3D printing: using DLP photocuring equipment to print and shape the fused quartz photocuring slurry obtained in step 2) to obtain a fused quartz ceramic green body.

[0080] 4) Degreasing of green body: Under argon atmosphere, heat to 215℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 320℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 380℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 450℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 650℃ at a rate of 0.1℃ / min, keep warm for 120min, finally heat to 800℃ at a rate of 0.2℃ / min, keep warm for 120min, cool with the furnace to complete degreasing.

[0081] 5) Ceramic sintering: In an air atmosphere, the temperature was raised to 600°C at a rate of 0.5°C / min, kept at this temperature for 180 min, then raised to 1150°C at a rate of 1°C / min, kept at this temperature for 180 min, and cooled in the furnace to obtain fused quartz ceramics with a flexural strength of 38.6 MPa.

[0082] Embodiment 5:

[0083] 1) Powder modification: 2 μm fused quartz powder was blended with 1 wt % stearic acid and 1 wt % polyethylene, and wet-milled for 12 h with alcohol added, wherein the mass ratio of alcohol to powder was 1:1. The modified fused quartz powder was obtained after drying and sieving.

[0084] 2) Preparation of photocurable slurry: The solid content of the photocurable slurry is 65 vol%; the photosensitive resin system is composed of a prepolymer of bisphenol A diglycidyl ether, polyurethane acrylate (PUA), a prepolymer of dicyclohexyl-1,4-dimethanol vinyl ether, a resin monomer of 1,6-hexanediol diacrylate (HDDA), trimethylolpropane triacrylate (TMPTA), a resin monomer of tripropylene glycol diacrylate (TPGDA), a photoinitiator of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide (TPO), and a photoinitiator of diaryliodonium salt, wherein the ratio of prepolymer 1, prepolymer 2, resin monomer 1 and resin monomer 2 is 1:3:8:8, the ratio of photoinitiator 1 to photoinitiator 2 is 2:1, and the total amount of photoinitiator 1 and photoinitiator 2 is 2wt% of the total mass of the photosensitive resin system; 4wt% of the dispersant Solsperse TM AC4380 was added to the photosensitive resin system and homogenized at a speed of 1000 r / min for 30 s using a homogenizer. Then, the modified fused quartz powder obtained in step 1) and 200 nm SiC powder were added. The amount of SiC powder was 5 wt% of the mass of the modified fused quartz powder. The system was homogenized at a speed of 2000 r / min for 2 min using a homogenizer to obtain a fused quartz ceramic photocuring slurry.

[0085] 3) Photocuring 3D printing: using DLP photocuring equipment to print and shape the fused quartz photocuring slurry obtained in step 2) to obtain a fused quartz ceramic green body.

[0086] 4) Degreasing of green body: Under argon atmosphere, heat to 180℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 250℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 300℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 500℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 600℃ at a rate of 0.1℃ / min, keep warm for 120min, finally heat to 700℃ at a rate of 0.2℃ / min, keep warm for 120min, cool with the furnace to complete degreasing.

[0087] 5) Ceramic sintering: In air atmosphere, the temperature was raised to 600°C at a rate of 0.5°C / min, kept for 180 minutes, then raised to 1300°C at a rate of 1°C / min, kept for 180 minutes, and cooled in the furnace to obtain fused quartz ceramics with a flexural strength of 48.7 MPa.

[0088] Embodiment 6:

[0089] 1) Powder modification: 3 μm fused quartz powder was blended with 6 wt % of adipic acid and 6 wt % of polypropylene, and wet-milled for 10 h with alcohol added, wherein the mass ratio of alcohol to powder was 1:1. The modified fused quartz powder was obtained after drying and sieving.

[0090] 2) Preparation of photocurable slurry: The solid content of the photocurable slurry is 60 vol%; the photosensitive resin system is composed of a prepolymer of bisphenol A diglycidyl ether, a prepolymer of dicyclohexyl-1,4-dimethanol vinyl ether, a resin monomer of pentaerythritol tetraacrylate (PPTTA), a resin monomer of isobornyl dimethacrylate (IBOMA), a tripropylene glycol diacrylate (TPGDA), a photoinitiator of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide (TPO), and a photoinitiator of dibenzoin dimethyl ether, wherein the ratio of prepolymer 1, prepolymer 2, resin monomer 1 and resin monomer 2 is 1:3:8:8, the ratio of photoinitiator 1 to photoinitiator 2 is 2.5:0.5, and the total amount of photoinitiator 1 and photoinitiator 2 is 5 wt% of the total mass of the photosensitive resin system; 2 wt% of the dispersant Solsperse TM W75 was added to the photosensitive resin system and homogenized at a speed of 1000 r / min for 45 s using a homogenizer. Then, the modified fused quartz powder obtained in step 1) and 300 nm SiC powder were added. The amount of SiC powder was 3 wt % of the mass of the modified fused quartz powder. The system was homogenized at a speed of 1800 r / min for 1 min using a homogenizer to obtain a fused quartz ceramic photocuring slurry.

[0091] 3) Photocuring 3D printing: using DLP photocuring equipment to print and shape the fused quartz photocuring slurry obtained in step 2) to obtain a fused quartz ceramic green body.

[0092] 4) Degreasing of green body: Under argon atmosphere, heat to 220℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 280℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 340℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 520℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 600℃ at a rate of 0.1℃ / min, keep warm for 120min, finally heat to 750℃ at a rate of 0.2℃ / min, keep warm for 120min, cool with the furnace to complete degreasing.

[0093] 5) Ceramic sintering: In an air atmosphere, the temperature was raised to 600°C at a rate of 0.5°C / min, kept at this temperature for 180 min, then raised to 1150°C at a rate of 1°C / min, kept at this temperature for 120 min, and cooled in the furnace to obtain fused quartz ceramics with a flexural strength of 40.6 MPa.

[0094] Comparative Example 1:

[0095] 1) Powder modification: 2 μm fused quartz powder was blended with 2.5 wt% KH570 and 2 wt% polyethylene glycol, and wet-milled for 12 h with alcohol added, the mass ratio of alcohol to powder being 1:1. The modified fused quartz powder was obtained after drying and sieving.

[0096] 2) Preparation of photocurable slurry: The solid content of the photocurable slurry is 65 vol%; the photosensitive resin system is composed of a prepolymer of bisphenol A diglycidyl ether, polyurethane acrylate (PUA), a prepolymer of dicyclohexyl-1,4-dimethanol vinyl ether, a resin monomer of 1,6-hexanediol diacrylate (HDDA), trimethylolpropane triacrylate (TMPTA), a resin monomer of tripropylene glycol diacrylate (TPGDA), a photoinitiator of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide (TPO), and a photoinitiator of diaryliodonium salt, wherein the ratio of prepolymer 1, prepolymer 2, resin monomer 1 and resin monomer 2 is 1:3:8:8, the ratio of photoinitiator 1 to photoinitiator 2 is 2:1, and the total amount of photoinitiator 1 and photoinitiator 2 is 2wt% of the total mass of the photosensitive resin system; 4wt% of the dispersant Solsperse TM 29000 was added into the photosensitive resin system, and homogenized for 30 seconds with a homogenizer at a speed of 1000 r / min. Then, the modified fused quartz powder obtained in step 1) and 200 nm SiC powder were added, and the amount of SiC powder was 6wt%. The mixture was homogenized for 2 minutes with a homogenizer at a speed of 2000 r / min to obtain a fused quartz ceramic photocuring slurry.

[0097] 3) Photocuring 3D printing: using DLP photocuring equipment to print and shape the fused quartz photocuring slurry obtained in step 2) to obtain a fused quartz ceramic green body.

[0098] 4) Degreasing of green body: Under argon atmosphere, heat to 180℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 250℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 300℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 500℃ at a rate of 0.1℃ / min, keep warm for 120min, then heat to 600℃ at a rate of 0.1℃ / min, keep warm for 120min, finally heat to 700℃ at a rate of 0.2℃ / min, cool with the furnace to complete degreasing.

[0099] 5) Ceramic sintering: In air atmosphere, the temperature was raised to 600°C at a rate of 0.5°C / min, kept at that temperature for 180min, then raised to 1200°C at a rate of 1°C / min, kept at that temperature for 180min, and cooled with the furnace to obtain fused quartz ceramics with a flexural strength of 28.6MPa. When the addition amount of SiC powder was 6wt%, there were SiC particles that were not oxidized and sintered, which led to a decrease in flexural strength.

[0100] The present invention provides a method for preparing high-strength fused quartz ceramic by photocuring. The high light absorbance of SiC powder is utilized and it is regarded as an inorganic dye to reduce the curing depth of slurry. At the same time, SiC is oxidized at high temperature to generate SiO2 in situ, so as to connect the original SiO2 particles and promote sintering densification.

[0101] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing high-strength fused quartz ceramics by photocuring, characterized in that: The following steps are involved: S1: Blending fused quartz powder with modifier 1 and modifier 2 to obtain a mixed powder, and then wet-grinding, drying and sieving to obtain modified fused quartz powder; S2: Prepolymer 1, prepolymer 2, resin monomer 1, resin monomer 2, photoinitiator 1, and photoinitiator 2 are mixed to prepare a photosensitive resin system; a dispersant is added to the photosensitive resin system and mixed evenly, and then modified fused quartz powder and SiC powder are added and mixed evenly to prepare a fused quartz ceramic photocuring slurry; S3: Printing and molding the fused quartz ceramic photocuring slurry to obtain a fused quartz ceramic green body; S4: degreasing the fused quartz ceramic green body to obtain a fused quartz degreasing part; S5: sintering the degreased fused quartz piece to obtain fused quartz ceramics; Wherein, S2, the amount of SiC powder is 1wt% to 5wt% of the mass of the modified fused quartz powder.

2. The method for preparing high-strength fused quartz ceramic by photocuring molding according to claim 1, characterized in that: In S1, the modifier 1 is one or more of KH550, KH560, KH570, stearic acid, oleic acid, palmitic acid, and adipic acid; the amount of the modifier 1 is 1wt% to 6wt% of the mass of the modified fused quartz powder; The second modifier is one or more of polyethylene, polypropylene, polyacrylamine, polymaleic acid, polyethylene glycol, polyacrylic acid, and sodium polyacrylate; the amount of the second modifier is 1wt% to 6wt% of the mass of the modified fused quartz powder.

3. The method for preparing high-strength fused quartz ceramic by photocuring molding according to claim 1, characterized in that: In S2, the solid content of the fused quartz ceramic photocuring slurry is 55 vol% to 65 vol%.

4. The method for preparing high-strength fused quartz ceramic by photocuring molding according to claim 1, characterized in that: In S2, the particle sizes of the modified fused quartz powder and the fused quartz powder are both 1 to 5 μm; and the particle size of the SiC powder is 200 to 500 nm.

5. The method for preparing high-strength fused quartz ceramic by photocuring molding according to claim 1, characterized in that: In S2, the prepolymer 1 is one or more of bisphenol A diglycidyl ether, brominated bisphenol F diglycidyl ether, polyurethane acrylate, and polyester acrylate; the prepolymer 2 is one or more of triethylene glycol divinyl ether, cyclohexyl-1,4-dimethanol vinyl ether, and vinyl acetate; the resin monomer 1 is one or more of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, and pentaerythritol tetraacrylate; the resin monomer 2 is one or more of isobornyl methacrylate, tripropylene glycol diacrylate, and dipentaerythritol hexaacrylate.

6. The method for preparing high-strength fused quartz ceramic by photocuring molding according to claim 1, characterized in that: In S2, the ratio of prepolymer 1, prepolymer 2, resin monomer 1, and resin monomer 2 is 1:3:8:

8.

7. The method for preparing high-strength fused quartz ceramic by photocuring molding according to claim 1, characterized in that: In S2, the photoinitiator 1 is one or two of 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide; the photoinitiator 2 is one or more of phenyl diazonium fluoroborate, diaryl iodonium salt, triaryl sulfonium salt and benzoin dimethyl ether.

8. The method for preparing high-strength fused quartz ceramic by photocuring molding according to claim 1, characterized in that: In S2, the mass ratio of the photoinitiator 1 to the photoinitiator 2 is 1.5-2.5:0.5-1.5; the total amount of the photoinitiator 1 and the photoinitiator 2 is 1wt%-5wt% of the total mass of the photosensitive resin system.

9. The method for preparing high-strength fused quartz ceramic by photocuring molding according to claim 1, characterized in that: In S2, the dispersant is selected from Solsperse TM 29000, Solsperse TM W210, Solsperse TM W75, Solsperse TM AC5160, Solsperse TM AC4380, the amount of the dispersant is 2wt% to 8wt% of the mass of the modified fused quartz powder.

10. The method for preparing high-strength fused quartz ceramic by photocuring molding according to claim 1, characterized in that: In S3, the printing and forming is performed by using a DLP light curing device; In S4, the degreasing process is as follows: Under argon atmosphere, the maximum degreasing temperature is 650-800°C, the heating rate is 0.1-0.2°C / min, the holding time is 120min, and the furnace is cooled; In S5, the sintering process is as follows: In an air environment, the sintering temperature is 1150°C to 1400°C, the heating rate is 0.5 to 1°C / min, the holding time is 120 to 180 minutes, and the furnace is cooled.

Citation Information

Patent Citations

  • Two-step sintering method based on 3D printing SiC-SiO2 ceramic green body

    CN114276143A

  • Silicon carbide ceramic slurry, preparation method thereof and pyrolysis process of photocuring molded body

    CN115180955A

  • A composition for preparing a ceramic product by stereolithography, a ceramic product, and a method of manufacturing a ceramic product

    EP4331841A1

  • Nanoporous ceramic for atomization core and preparation method thereof

    US20230331632A1